1995
DOI: 10.1007/bf00020237
|View full text |Cite
|
Sign up to set email alerts
|

Frequent in-frame length variations are found in the diverged simple repeat sequences of the protein-coding regions of two putative protein kinase genes of Brassica napus

Abstract: Two putative protein kinase cDNA clones were isolated from Brassica napus by screening with a putative protein kinase cDNA clone of Arabidopsis thaliana. The deduced amino acid sequences show a distinct modular composition, consisting of a possible protein kinase catalytic region at the amino terminus and a highly acidic region encoded from diverged simple repeat sequences at the carboxy terminus. Comparison of the nucleotide sequences encoding this acidic region revealed a high rate of in-frame length variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…They may result from DNA mispairing between two adjacent, short, directrepeat sequences (Tautz et al, 1986;Levinson and Gutman, 1987). Similar sequence length variations have also been observed in protein kinases (Park et al, 1995) and prolinerich cell wall proteins (Schmidt et al, 1994).…”
Section: Discussionsupporting
confidence: 70%
“…They may result from DNA mispairing between two adjacent, short, directrepeat sequences (Tautz et al, 1986;Levinson and Gutman, 1987). Similar sequence length variations have also been observed in protein kinases (Park et al, 1995) and prolinerich cell wall proteins (Schmidt et al, 1994).…”
Section: Discussionsupporting
confidence: 70%
“…An amino acid sequence comparison between SPK-3 and SPK-4 reveals 93% overall sequence identity and 95% identity within the catalytic domain. Homology searches in databases (GenBank, EMBL and PIR) using the catalytic domain of SPK-3 (from Met 1 to Phe 260 ) showed that the two SPKs are closely related to the Arabidopsis ASK2 protein kinase (91% identity; Park et al 1993) and an ABA-inducible protein kinase, PKA-BA1 (82% identity; Anderberg and Walker-Simmons, 1992), from wheat. Although the degree of identity was relatively low, at 30±40%, [SPK-3 and SPK-4 also showed] sequence similarity to yeast SNF1 (Celenza and Carlson, 1986), barley cBKIN12 (Halford et al 1992), yeast nim1 + (Russell and Nurse, 1987), yeast Ca 2+ / calmodulin-dependent protein kinase (Ohya et al 1991), and soybean CDPK (Harper et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…SPK-3 and SPK-4 contain highly acidic regions at their C-terminal ends which are thought to represent the regulatory domains of these kinases (Park et al 1993). The acidic regions encoded by the SPK-3 and SPK-4 cDNA clones contain stretches of 18 and 16 Glu/Asp residues (amino acid positions, 317 to 334 and 317 to 332), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The B. napus C genome has been identified and mapped in a number of Brassica populations by several groups and has been determined to comprise nine linkage groups: N11-N19 (Slocum et al 1990;Park et al 1995;Sharpe et al 1995;Piquemal et al 2005;Sun et al 2007). Using the approaches described above, we identified the nine C-genome chromosomes of B. carinata.…”
Section: Generation Of B-genome Interspecific Linesmentioning
confidence: 99%